1999
DOI: 10.1002/1529-0131(199906)42:6<1088::aid-anr4>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-negative p53 mutations in rheumatoid arthritis

Abstract: Objective. Studies were performed to determine if p53 mutations identified in rheumatoid arthritis (RA) synovial tissue are dominant negative.Methods. Site-directed mutagenesis was used to produce 2 RA-derived mutants: asparagine3serine at codon 239 (N239S) and arginine3stop at codon 213 (R213*). HS68 dermal fibroblasts were transfected with either empty vector, wild-type p53 cDNA (wt), or the N239S or R213* mutant p53 cDNA clones. Interleukin-6 (IL-6) and bax gene expression were determined by Northern blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
68
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 16 publications
6
68
1
Order By: Relevance
“…IL-6 is a key proinflammatory cytokine that is abundant in RA synovium and synovial tissue (46,47) and its transcription is suppressed by wild-type p53 (27). We have shown that some p53 mutations from RA patients interfere with the ability of wild-type p53 to inhibit IL-6 gene expression (23). Real-time PCR analysis of microdissected synovium indicated that those regions that had abundant p53 mutations expressed significantly greater amounts of IL-6 mRNA compared with regions containing predominantly wild-type p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 is a key proinflammatory cytokine that is abundant in RA synovium and synovial tissue (46,47) and its transcription is suppressed by wild-type p53 (27). We have shown that some p53 mutations from RA patients interfere with the ability of wild-type p53 to inhibit IL-6 gene expression (23). Real-time PCR analysis of microdissected synovium indicated that those regions that had abundant p53 mutations expressed significantly greater amounts of IL-6 mRNA compared with regions containing predominantly wild-type p53.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the p53 mutations in RA are characterized by transition base changes (7,21) and have also been previously identified in human neoplastic tissue (22). Furthermore, certain p53 mutations in RA are dominant negative and can suppress endogenous wild-type p53 function (23). Inactivation of p53 protein can recapitulate many of the phenotypic changes observed in RA, such as increased proliferation and invasion of synovial cells (24,25).…”
mentioning
confidence: 95%
“…Thus, p21-deficeint synovial fibroblasts behave similarly to the RA synovial fibroblasts that lack p53 or express the mutant forms of p53. Furthermore, ectopic expression of p21 or overexpression of wild-type p53 reduces IL-6 and MMP-1 expression in RA synovial fibroblasts (53)(54)(55)(56)58). Collectively, these data suggest that p21 may be one of the nodal points through which p53 inhibits cytokines and MMPs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that a subset of synovial fibroblasts may possess an inactive form of p53. Overexpression of plasmids encoding the p53 mutants found in RA synovium suppresses wild-type p53 function, as indicated by the induction of known p53-regulated genes, including IL-6 (53,54) and MMP-1 (55,56), which are normally inhibited by wild-type p53. Additionally, mice deficient in p53 display enhanced experimental arthritis, elevated levels of IL-6 in the synovium, and increased spontaneous MMP-13 expression compared with wildtype mice (57).…”
Section: Discussionmentioning
confidence: 99%
“…However, p53 expression is also upregulated during inflammation and infections. Synovia from rheumatoid arthritis patients exhibit dominant negative mutations of p53 and expression of p53 is also upregulated in the joints of these patients [6]. This increased level of p53 in arthritic synovium joints can be seen in the early stages of disease development [7].…”
Section: Introductionmentioning
confidence: 99%